Designing, Validation, and Feasibility of Integrated Approach of Heartfulness Meditation and Yoga Protocol (IAHFNM & YP) for Hypertensive Participants - Pooja S. Singh; Veronique Nicolai; Yogesh Patil; Neelam Yeram; Bhusan Bhukte; Kapil Thakur; Mitesh Thakker; Haresh Mehta; Mansee K. Thakur (Hindawi-Wiley, 2024)
The module was designed and developed at Heartfulness Institute, Kanha Shanti Vanam, Hyderabad. The Department of Medicine, MGM Medical College & Hospital, MGMIHS, Navi Mumbai, carried out the validation and subsequently pilot-tested on volunteers. Forty experts were selected to validate the contents of IAHFNM & YP which was designed after a thorough review of meditation and yoga literature. A total of 23 items were included, and each item was rated as essential or not essential by the experts, based on which the content validity ratio (CVR), Item-Level Content Validity Index (I-CVI), and Scale-Level Content Validity Index Average (S-CVI/Ave) were calculated. Reliability analysis and a pilot study for the feasibility of IAHFNM & YP for hypertensive patients were also done. All 23 practices exhibited significant CVR (≥ 0.29), I-CVI (> 0.79), and S-CVI/Ave (> 0.9); thus, the tool was found to have valid contents. Cronbach's alpha value for the tool was 0.95 which was highly reliable. Feasibility analysis in hypertensive participants showed that the tool is reliable and implementable. The IAHFNM & YP tool designed for hypertensive patients is valid, reliable, and feasible. The patients showed a willingness to continue with heartfulness meditation and yoga practices for participation in research for a longer duration. Further studies to confirm the tool's efficacy should be conducted with a large sample size.